Aberrant expression of sLex and sLea as candidate prognostic factors for feline mammary gland tumour. Issue 4 (April 2014) - Yoshida, Saori; Yoshida, Kota; Jaroensong, Tassanee; Lee, Soo-Jung; Kamida, Ayako; Saeki, Kohei; Fujita, Naoki; Nishimura, Ryohei; Sasaki, Nobuo; Nakagawa, Takayuki
Expression of the carbohydrate antigens sialyl Lewis x (sLe x ) and a (sLe a ) was evaluated in feline mammary gland tumours (FMGT). Immunohistochemical analysis of tissues from 21 FMGT patients and 11 healthy cats revealed significantly higher sLe x and sLe a antigen expression in adenocarcinoma tissues compared with that of normal mammary tissues ( P <0.01). Serum concentration of sLe x was evaluated using an enzyme-linked immunosorbent assay and was significantly higher in the 11 FMGT patients (4.71 ± 10.1 U/ml) than the 22 patients with other disease (2.69 ± 1.59 U/ml) ( P = 0.03) and the 22 healthy cats (3.71 ± 1.10 U/ml), although the latter difference was not significant. Although the number of cases examined in this study was small, our findings suggest that aberrant expression of sLe antigens may be induced by tumourigenesis in FMGT and that sLe antigens are potential prognostic tumour markers for FMGT.